2001
DOI: 10.1038/nm1101-1217
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef associated PAK and PI3-Kinases stimulate Akt-independent Bad-phosphorylation to induce anti-apoptotic signals

Abstract: A highly conserved signaling property of Nef proteins encoded by human or simian immunodeficiency virus is the binding and activation of a PAK kinase whose function is unclear. Here we show that Nef-mediated p21-activated kinase (PAK) activation involves phosphatidylinositol 3-kinase, which acts upstream of PAK and is bound and activated by Nef similar to the manner of Polyoma virus middle T antigen. The Nef-associated phosphatidylinositol-3-PAK complex phosphorylated the pro-apoptotic Bad protein without invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
223
4
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(237 citation statements)
references
References 46 publications
8
223
4
2
Order By: Relevance
“…Recent studies have shown that Nef inhibits death receptor-mediated apoptosis by interacting with apoptosis signal regulating kinase 1 and blocking its activity in T cells (12). More recently, it has been demonstrated that HIV-1 Nef also suppresses apoptosis by stimulating Akt-independent Bad phosphorylation through PI3K and PAK pathways in T lymphocytes (13). In contrast to these studies, we found that Nef-induced survival does not require PI3K activity (Fig.…”
contrasting
confidence: 91%
See 2 more Smart Citations
“…Recent studies have shown that Nef inhibits death receptor-mediated apoptosis by interacting with apoptosis signal regulating kinase 1 and blocking its activity in T cells (12). More recently, it has been demonstrated that HIV-1 Nef also suppresses apoptosis by stimulating Akt-independent Bad phosphorylation through PI3K and PAK pathways in T lymphocytes (13). In contrast to these studies, we found that Nef-induced survival does not require PI3K activity (Fig.…”
contrasting
confidence: 91%
“…In addition, Nef suppresses T-cell apoptosis initiated by serum starvation or HIV replication. In this case, Nef was shown to induce serine phosphorylation of Bad, the mitochondrial pro-apoptotic mediator, through a previously described p21-activated protein kinase known to associate with Nef (13).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…It is not plausible that HIV has evolved a highly specific mechanism by which Tat kills off only bystander cells; thus, it is possible that two HIV-encoded proteins control the activities of the main regulators of the mitochondrial apoptotic pathway in infected cells. HIV-1 Nef activates the phosphatidylinositol 3-kinase⅐p21-activated kinase complex, which inactivates the pro-apoptotic Bad protein by phosphorylation (70), and HIV-1 Vpr activates the down-modulation of the pro-apoptotic Bax protein and up-regulates the levels of the anti-apoptotic Bcl-2 protein (71). Thus, Nef and Vpr possibly counteract the effects of Tat in infected cells and protect the infected cells from apoptosis.…”
Section: Ug05rp Induces Greater Up-regulation Of Fasl Mrna Compared Wmentioning
confidence: 99%
“…Nef produced during HIV replication enhances expression of the Fas ligand (FasL) on the surface of infected cells, causing apoptosis of bystander cells through FasL-Fas cross-linking (9). On the other hand, Nef protects the infected cells from apoptosis by inhibition of the apoptosis signal-regulating kinase 1 (ASK1) or inhibition of the proapoptotic protein Bad through increased phosphorylation by the p21-activated kinase (10,11).…”
Section: Hiv-1mentioning
confidence: 99%